The Influence of Leadership Style on Employee Performance: The Role of Employee Motivation at PT AHI Tbk - Ahmad Munawar, Niknik; Hadiaty, Fifit (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the impact of leadership style, work environment, and motivation on employee performance at PT. AHI Tbk. Using a quantitative method with a sample of 200 employees, data were analyzed using Smart PLS 3. The results indicate that leadership style has a significant effect on employee performance, with a t-statistic of 4.326 and a p-value of 0.000. Conversely, the work environment did not show a significant effect on employee performance, as evidenced by a t-statistic of 1.253 and a p-value of 0.211. Additionally, motivation did not function as a significant mediator between leadership style and employee performance. These findings suggest that improving employee performance can be achieved through the development of effective leadership styles, although the work environment aspects require further evaluation. The recommendations generated from this study include enhancing leadership training programs, improving working conditions, and focusing on employee motivation development. This research is expected to provide insights for management and stakeholders to improve employee performance through a more holistic approach.